The Livable Corridor as a Generator of Urban Activity: The Case of Simpang Lima Corridor, Ampenan Old Town - Al Giffari, Muh Haikal; Roychansyah, Muhammad Sani (Jurnal Planologi, 2025)
ABSTRACTTo date, the relationship between corridor livability and the generation of activity in cultural heritage areas has rarely been examined empirically, particularly in the context of cities in Indonesia. Kota Tua Ampenan, one of the heritage areas in Mataram City, has the potential to become an urban tourism destination due to its Art Deco architecture. However, the decline in the area's vitality, reflected in the condition of neglected historic buildings and the lack of public space activities, indicates that the corridor's function as a catalyst for the area's vitality is not yet optimal. This study aims to analyze the influence of four livability factors-accessibility, land use, comfort and safety, and memorability-on activity generation in the Simpang Lima Corridor. The method used is a quantitative descriptive approach with multiple linear regression techniques using SPSS. The results show that the four factors collectively contribute 78% to activity generation (Adjusted R² = 0.78), with accessibility, comfort and safety being the dominant factors. These findings suggest that improving the livability quality of the corridor can effectively promote the reactivation of heritage areas. This study makes an important contribution to the development of a theoretical approach to livability-based design in historic urban corridors, which can serve as a strategic reference for revitalization efforts in old cities in Indonesia and Southeast Asia.Keywords: Activity Generator, Corridor Design, Cultural Heritage Spaces, Livable Corridors, Pedestrian Ways. ABSTRAKHingga saat ini, keterkaitan antara livabilitas koridor dan pembangkitan aktivitas di kawasan warisan budaya masih jarang ditelaah secara empiris, khususnya dalam konteks kota-kota di Indonesia. Kota Tua Ampenan, salah satu kawasan warisan di Kota Mataram, menyimpan potensi sebagai destinasi pariwisata perkotaan melalui karakter arsitektur Art Deco. Namun, penurunan vitalitas kawasan yang tercermin dari kondisi bangunan bersejarah yang terbengkalai dan minimnya aktivitas ruang publik menunjukkan belum optimalnya fungsi koridor sebagai pemicu kehidupan kawasan. Penelitian ini bertujuan untuk menganalisis pengaruh empat faktor livabilitas yaitu, aksesibilitas, penggunaan lahan, kenyamanan dan keamanan, serta memorabilitas, terhadap pembangkitan aktivitas di Koridor Simpang Lima. Metode yang digunakan adalah pendekatan deskriptif kuantitatif dengan teknik regresi linier berganda dengan aplikasi SPSS. Hasil penelitian menunjukkan bahwa keempat faktor secara simultan berkontribusi sebesar 78% terhadap pembangkitan aktivitas (Adjusted R² = 0,78), dengan aksesibilitas serta kenyamanan dan keamanan sebagai faktor dominan. Temuan ini menunjukkan bahwa peningkatan kualitas livabilitas koridor dapat mendorong reaktivasi kawasan warisan secara lebih efektif. Studi ini memberikan kontribusi penting dalam pengembangan pendekatan teoritis perancangan berbasis livability pada koridor perkotaan bersejarah, yang dapat menjadi acuan strategis dalam upaya revitalisasi kota lama di Indonesia maupun Asia Tenggara.Kata Kunci: Jalur Pejalan Kaki, Kawasan Cagar Budaya, Livabilitas Koridor, Pembangkitan Aktivitas, Penataan Koridor.